The prime minister - Trollope, Anthony, 1815-1882.; McCormick, John, 1918-; Uglow, Jennifer S. (Oxford [Oxfordshire] ; New York : Oxford University Press, 1983)
Much against his will, the Duke of Omnium consents to lead a coalition government. The Duchess quickly becomes a social figure of great power: with abounding and sometimes indiscriminate hospitality she strives to consolidate his support. Together they make their way to the centre of society and, like Phineas Finn before them, they find it hollow.
Bibliography: p. xxiv-xxv.
Keywords: Palliser, Plantagenet (Fictitious character) -- Fiction; Prime ministers -- Fiction; London (England) -- Fiction; Political fiction